Certain Structure of Lagrange's Theorem with the Application of Interval-Valued Intuitionistic Fuzzy Subgroups. (24th February 2022) - Kattan, Doha A.; Amin, Maria; Bariq, Abdul
Abstract : This paper presents the concept of an interval-valued intuitionistic fuzzy subgroup defined on interval-valued intuitionistic fuzzy sets. We study some of the fundamental algebraic properties of interval-valued intuitionistic fuzzy cosets and interval-valued intuitionistic fuzzy normal subgroup of a given group. This idea is used to describe the interval-valued intuitionistic fuzzy order and index of interval-valued intuitionistic fuzzy subgroup. We have created numerous algebraic properties of interval-valued intuitionistic fuzzy order of an element. We also prove the interval-valued intuitionistic fuzzification of Lagrange's theorem.